Ilang Katagang Filipino bilang Bukal ng Pamimilosopiya - Clemente, Noel L (Archīum Ateneo, 2018)
: Despite Roque J. Ferriols's initiative of teaching philosophy in the Filipino vernacular, many philosophy teachers in the Philippines still use primarily European thinkers, albeit translating their ideas into Filipino. Emerita S. Quito questions the suitability of the Filipino language for philosophizing: can we philosophize in Filipino without merely translating Western ideas? In this paper, I want to dispel Quito's doubts by examining Filipino words that are rich in philosophical meaning, which, I argue, are not merely translations of European ideas. I focus my discussion on key terms in teaching Philosophy of the Human Person: how ‘pagninilay’ describes what philosophizing is, how ‘pagkakataon’ captures the historicity of the human person, and how ‘tao po’ illustrates what philosophy of the human person is about, within a particularly Filipino experience. Through these Filipino terms, I hope to show that our language is indeed rich in philosophical insight.